Modelling evaporation from a drained and rewetted peatland - Spieksma, J.F.M.; Moors, E.J.; Dolman, A.J.; Schouwenaars, J.M. (Journal of hydrology (Amsterdam), 1997)
Evaporation from a cutover raised bog in The Netherlands was modelled using a detailed, physically based evaporation model for heterogeneous vegetation and unsaturated soil water flow “SWAPS”. The model enables a quantification of the role of heterogeneity on evaporation. Micro-meteorological measurements above a vegetation of Molinia caerulea (purple moor grass) in the cutover raised bog “Engbertsdijksvenen” are used for calibration and validation of the model. In the present study, it is investigated how small scale heterogeneity affects the prediction of evaporation. Therefore, two hypothetical variants, which represent two possible types of small scale heterogeneity in peatlands, are evaluated: (1) peatland in which drainage has resulted in a vegetation cover of 50% purple moor grass and 50% birch, (2) peatland in which after rewetting the vegetation consists of 50% purple moor grass and 50% Sphagnum mosses. The results show that characteristics of the evaporation from purple moor grass in the two variants are dissimilar. The evaporation from purple moor grass, forming the lower components of a vegetation stand (variant 1), can be accurately predicted via radiation based models. In case purple moor grass is the exposed part of the vegetation (variant 2), such models are not likely to predict the evaporation from purple moor grass correctly. An exposed, aerodynamically rough vegetation requires a model that accounts for the vapour pressure deficit as well.